Parasite acquisition by larval coral‐reef fishes - K. Peyrusse; P. Sasal; D. Lecchini (Journal of Fish Biology, 2012)
Of 164 fish larvae belonging to 11 species sampled from the island of Moorea, French Polynesia, 30% had at least one parasite individual and parasite prevalence ranged between 0 for Chaetodon citrinellus and 80% for Parupeneus barberinus . Parasites were present only in larvae that had fed and were present in the gut but absent from gills, body cavity and muscle. Parasites appeared to be acquired by ingestion of intermediate hosts when the larvae fed on the outer slope, prior to reef colonization.